2015
DOI: 10.1118/1.4915079
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of spatial resolution in breast CT at UC Davis

Abstract: Purpose: Dedicated breast computed tomography (bCT) technology for the purpose of breast cancer screening has been a focus of research at UC Davis since the late 1990s. Previous studies have shown that improvement in spatial resolution characteristics of this modality correlates with greater microcalcification detection, a factor considered a potential limitation of bCT. The aim of this study is to improve spatial resolution as characterized by the modulation transfer function (MTF) via changes in the scanner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 25 publications
3
67
1
Order By: Relevance
“…showed that the low electronic noise of CMOS detectors enables improved angular sampling by lowering the required dose per frame. In breast CBCT, Gazi et al . and Shen et al .…”
Section: Introductionmentioning
confidence: 99%
“…showed that the low electronic noise of CMOS detectors enables improved angular sampling by lowering the required dose per frame. In breast CBCT, Gazi et al . and Shen et al .…”
Section: Introductionmentioning
confidence: 99%
“…A critical requirement for a breast cancer diagnostic device is the ability to accurately detect micro‐calcification as they are frequently associated with malignancy . To date, many efforts have been exerted to optimize the detector performance of CBBCT system for better detection of micro‐calcifications, but there have not been any studies to investigate the dependency of OFR. The results presented in this study show that the OFR has a significant impact on the image quality in terms of spatial resolution and contrast, and this effect is especially prominent for fine structures (i.e., micro‐calcifications) in CBBCT images.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…For low input kVp’s, Lα 2 , Lβ 4 and Lγ 1 were easily differentiated, while Kα 2 , Kα 1 and Kβ 1 were differentiated for higher kVp values (80–130 kVp). Pulsed x-ray sources have shown a valuable spatial resolution improvement in breast imaging with cone beam CTs [42]. We can expect that the pulsed emission mode, when synchronized with the digital detectors in cone beam CTs and digital tomosynthesis imaging modalities, will likely improve the spatial resolution, reduce the scattering, and reduce the radiation dose levels.…”
Section: Discussionmentioning
confidence: 99%